Keterkaitan Dinamika Migrasi dengan Perubahan Paradigma Pertanian di Indonesia - Rani Andriani Budi Kusumo; Ganjar Kurnia; Iwan Setiawan; Riwanto Tirtosudarmo (Society, 2023)
The nexus between migration and agricultural transformation encapsulates the dynamics of rural community livelihoods. Existing studies have not explicitly delineated the landscape of out-migration from rural regions in Indonesia. This study aims to elucidate migration behaviors intertwined with the lives of farming households and the utilization of remittances for agricultural investment activities. Through a comprehensive examination of literature and meta-analyses encompassing various migration cases in Indonesia, the findings reveal that both local and international migration by rural residents illustrate the adaptive strategies employed by households to cope with constrained income within the agricultural sector and limited employment prospects outside it in their villages. The enduring bond of rural communities with the agricultural sector aligns with the discernible pattern of remittance utilization, where a portion is earmarked for agricultural investments, such as land acquisition, including rice fields. The outcomes of this meta-analysis offer a holistic perspective on the relationship between migration and agriculture in Indonesia, serving as a foundation for optimizing the potential of migrants through well-tailored reintegration strategies aimed at mitigating poverty in rural areas.